An improved protocol for micropropagation of saltbush (atriplex) species - I. Reyes-Vera; M.E. Lucero; J.R. Barrow (Native Plant Journal, 2010)
Atriplex griffithsii Standl is a threatened halophytic shrub found in saline soils of isolated regions within the desert basins in Southern New Mexico and Arizona. A related species within the genus, A. canescens, has been successfully micropropagated, suggesting that clonal propagation may offer a strategy to produce large numbers of A. griffithsii plants for conservation, restoration, or research needs. However, previously reported A. canescens micropropagation protocols could not be reproduced with A. griffithsii. Here we evaluated rates of shoot production of A. griffithsii explants exposed to varied growth regulator treatments. Maximal shoot productivity was observed with explants exposed to 1.14 µM indole 3-acetic acid (IAA) + 24.61 µM 6-('-'-dimethylallylamino) purine (2iP). Rooting frequencies of 55% were observed on hormone free medium. Results demonstrate potential to micropropagate clonal A. griffithsii, a species with potential for restoration of saline soils.

Hyperhydricity reversal and clonal propagation of fourwing saltbush (Atriplex canescens, Chenopodiaceae) cultivated in vitro - I. Reyes-Vera; Potenza, C.L.; J.R. Barrow (Australian Journal of Botany, 2008)
In vitro propagated shoots of fourwing saltbush [Atriplex canescens (Pursh Nutt)] showed severe symptoms of hyperhydricity. Hyperhydricity is a frequent physiological problem reported in micropropagation of A. canescens and other plant species, and drastically reduces the quality of in vitro cultures. It is exacerbated when plants are cultured in airtight culture vessels on medium formulations with high nitrogen concentrations. We show that the reversion of hyperhydric A. canescens shoots to normal shoots was significantly affected by the presence of inorganic nitrogen in the culture vessel. When the culture vessel was vented or when ammonium nitrate was deleted from Murashige and Skoog basal medium, rates of reversion were significantly higher. While statistically significant differences were evident when comparing vented vs. non-vented treatments for each medium, the modified culture medium with vented closures was consistently the best treatment, showing a total cumulative frequency of 39.7% compared with a total cumulative frequency of 7.1 % observed in the control treatment. Resulting normal shoots also showed significant improvements in further manipulations, including rooting in vitro, transplantation to soil, and survival in native sites.
Keywords: botany; clonal; fourwing; hyperhydricity; saltbush

Plant inoculation with obligate endophytes from arid rangelands grasses: Implications for water usage - I. Reyes-Vera; M.E. Lucero; J.R. Barrow (Symposium on Efficient Water Use in the Urban Landscape, 2006)
Endophytic inoculation of grasses can result in significant agronomic advantages including increased drought tolerance and disease resistance as well as enhanced water and nutrient uptake. While some endophytes can increase plant toxicity, others are thought to be strictly beneficial. New attempts to induce novel grass-endophyte associations with harmless endophytes are needed. By means of a novel biotechnology technique, we have transferred obligate biotrophic fungal endophytes from local rangeland grass species to novel host grasses. Important differences in root growth habbit and shoot/root ratio were apparent. Implications for plant water and nutrient uptake are discussed.
Keywords: disease resistance; drought tolerance; endophytic; inoculation